2021
DOI: 10.1111/jfpp.15296
|View full text |Cite
|
Sign up to set email alerts
|

High‐pressure treatment of silver pomfret ( Pampus argenteus ): Inactivation of Listeria monocytogenes , impact on amino acid profile, and changes during storage in fatty acid compositions

Abstract: Seafood or fish are a good source of high-quality protein, lipids, vitamins, and micro-elements, and are recognized to play a vital role in human health and nutrition (Ganguly et al., 2018). Seafood proteins are easily digestible and are rich in amino acids such as glutamic acid, aspartic acid, arginine, lysine, and leucine, some of which are deficient in cereal-based diets (Erkan & Özden, 2007). The consumption of marine fish is considered to have added benefits because of the presence of highly unsaturated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…A large number of high-pressure research works on various fish and fish products have been reported (Ahmed et al, 2021;Chouhan et al, 2015). HP-treatment confirmed a significant change in the quality indices (microstructure, color, texture, and biochemical indices) of abalone muscle at pressure treatment of 500 MPa/8 min or 550 MPa/3-5 min while compared with raw abalone meat (Briones-Labarca et al, 2012).…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…A large number of high-pressure research works on various fish and fish products have been reported (Ahmed et al, 2021;Chouhan et al, 2015). HP-treatment confirmed a significant change in the quality indices (microstructure, color, texture, and biochemical indices) of abalone muscle at pressure treatment of 500 MPa/8 min or 550 MPa/3-5 min while compared with raw abalone meat (Briones-Labarca et al, 2012).…”
mentioning
confidence: 84%
“…All samples (without pressure treatment, without inoculation, and pressure-treated) were enumerated by spread plating using appropriate dilution on the "0" day and after 30 days onto PALCAM Listeria-specific agar following the method described earlier for the HP-treated pomfret fish (Ahmed et al, 2021). In brief, fish sample (100 g) was taken in a stomacher bag, and 900-ml deionized water was added to prepare slurry.…”
Section: Microbial Enumerationmentioning
confidence: 99%
See 1 more Smart Citation